KAJIAN STRUKTURAL JEMBATAN PRECAST PRESSTRESS SANGKULIRANG –BATU LEPOK AMPANAS KABUPATEN KUTAI TIMUR - Muhammad Yasin (KURVA MAHASISWA, 2016)
Precast Prestressed Bridge is one of the various types of bridges that can be used to connect one edges of the land to the next edge of the mainland, but the ability to effectively Precast Prestressed Bridge just 30 meters onwards (Bambang Supriadi 2007), so the existence of the bridge this type are widely encountered in the long span landscape.The condition of District Sangkulirang bridge that is no longer feasible to pass a vehicle which includes agricultural and plantation local community, becoming an important reason to do research in the area. For the prevalence development of a region, badly needed roads and bridges infrastructure that are adequate in order to facilitate the conduct of the early stages of development in areas that are still isolated.From the analysis, it is concluded that the reinforcement needs of each different structural elements, reinforcing the need starting from a diameter of 8 mm, 10 mm, 12 mm, 16 mm, 19 mm , 25 mm and 32 mm. For pile foundation used a diameter of 40 cm, a depth of 18 meters in a state of End Bearing, and it takes 60 dots stake.